Comparison of Light Intensity under the Canopy between Sal (Shorea robusta) and Akashmoni (Acacia auriculiformis) in Agroforestry Stands: Effect of Tree Size and Distance from Individual Trees - Islam, Md. Al Forhad; Pitol, Md. Najmus Sayadat; Khan, Md. Nabiul Islam (Journal of Tropical Biodiversity and Biotechnology, 2023)
Agroforestry is now inevitable for meeting the snowballing demand for food of the growing number of people worldwide. The light environment is the most important driving force for the growth and development of crops in agroforestry stand. The present study aims to quantify the light interception in two different agroforestry types, where one was composed of Shorea robusta (Sal) with Ananas comosus and another was Acacia auriculiformis (Akashmoni) with Ananas comosus. The relative Photosynthetically Active Radiation (PAR) was measured by a pair of quantum sensors in four directions from some individual trees. Spatial variation of PAR was also explored in both stand types. The results revealed that RPAR did not significantly (P>0.05) vary among four directions of individual trees in S. robusta but the A. auriculiformis showed a significant difference (P<0.001) along the four directions. Also, RPAR was significantly different (P<0.001) at different distances from individual trees under the canopy of both tree species. When the stand-level spatial variation of RPAR was considered, A. auriculiformis (0.177) and S. robusta (0.171) showed no significant difference (P>0.05) in the light environment. Our findings explored that both the tree species would be suitable species for agroforestry practices in the area. For the betterment of the natural S. robusta forest responsible authorities should encourage people to avoid A. auriculiformis plantations near the natural S. robusta forest which will enhance the conservation of S. robusta cover in its natural habitat.